Empirical BAC factors method application to two real case studies in South Italy. (1st December 2021) - Bonomolo, Marina; Zizzo, Gaetano; Ferrari, Simone; Beccali, Marco; Guarino, Stefania
Abstract: The application of Building Automation and Control (BAC) systems has many advantages. One of these is the reduction of the end-user electricity consumption and, if applied to lighting systems, the achievement of well-acknowledged benefits from daylight, such as productivity, health, visual comfort and well-being. Concerning the first aspect, the international Standard EN 15232 proposes the so-called BAC Factors (BF) method to assess the impact of BAC systems on the final energy consumption. The method provides a simplified estimation of the energy savings due to automation in buildings and questions arise on its applicability in some situations. For this reason, the authors have carried out an experimental study aiming at comparing the energy savings calculated using the simplified BAC factor method with those evaluated with a measurement campaign on a laboratory setup. In particular, the BF are evaluated for an office and a residential environment, using sets of data measured in two cases study in South Italy by testing two lighting control systems in different end-uses (residential and office). The comparison between the sets of data shows the limits of the simplified BAC factor method. Highlights: The application of Building Automation and Control (BAC) systems has many recognized advantages. BAC factors method was applied for a real daylight linked control system and evaluated for an office and a residential case. Consumption calculated has been compared with consumption measured for a real case study. The comparison between the two set of data shows the limits of the simplified BAC factor method.